Numerical Simulation of Dispersion and Ventilation of Hydrogen Clouds in Case of Leakage Inside a Large-Scale Industrial Building - Khaled Yassin; Stephan Kelm; Ernst-Arndt Reinecke (Hydrogen, 2025)
As the attention to using hydrogen as a potential energy storage medium for power generation and mobility increases, hydrogen production, storage, and transportation safety should be considered. For instance, hydrogen’s extreme physical and chemical properties and the wide range of flammable concentrations raise many concerns about the current safety measures in processing other flammable gases. Hydrogen cloud accumulation in the case of leakage in confined spaces can lead to reaching the hydrogen lower flammability limit (LFL) within seconds if the hydrogen is not properly evacuated from the space. At Jülich Research Centre, hydrogen mixed with natural gas is foreseen to be used as a fuel for the central heating system of the campus. In this work, the release, dispersion, formation, and spread of the hydrogen cloud in the case of hydrogen leakage inside the central utility building of the campus are numerically simulated using the OpenFOAM-based containmentFOAM CFD codes. Additionally, different ventilation scenarios are simulated to investigate the behavior of the hydrogen cloud. The results show that locating exhaust openings close to the ceiling and the potential leakage source can be the most effective way to safely evacuate hydrogen from the building. Additionally, locating the exhaust outlets near the ceiling can decrease the combustible cloud volume by more than 25% compared to side openings far below the ceiling. Also, hydrogen concentrations can reach the LFL in case of improper forced ventilation after only 8 s, while it does not exceed 0.15% in the case of natural ventilation under certain conditions. The results of this work show the significant effect of locating exhaust outlets near the ceiling and the importance of natural ventilation to mitigate the effects of hydrogen leakage. The approach illustrated in this study can be used to study hydrogen dispersion in closed buildings in case of leakage and the proper design of the ventilation outlets for closed spaces with hydrogen systems.